2019
DOI: 10.17659/01.2019.0011
|View full text |Cite
|
Sign up to set email alerts
|

Metastasis of Renal Cell Carcinoma to Mandible

Abstract: Background: Renal cell carcinoma (RCC) is one of the most common urological malignancies. Case Report: A 62-year-old male patient was admitted to our clinic due to painful swelling on the right side of his face. On the panoramic radiograph, a well defined, unilocular, approximately 1.9×1.5 cm sized radiolucent area was observed. It was decided to enucleate the lesion, which was thought to be 'radicular cyst' radiographically. While performing incision and flap operations, bleeding continued in an abnormal amou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Twenty-seven patients exhibited bleeding [8, 10-14, 16, 17, 19, 21-24, 26, 28, 30, 31, 38, 39, 43, 48, 50, 55, 58, 61], which resulted in death in one case [58]. Ten patients reportedly had di culty with hemostasis during biopsy or surgery [10,22,26,38,48,52,61,63,66] .Three patients underwent preoperative vascular embolization or ligation, which did not lead to complications during surgery [15,19,26]. Our experience with the present patient also indicated that preoperative vascular embolization is helpful in preventing massive hemorrhage during surgery for pulsatile oral metastasis of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…Twenty-seven patients exhibited bleeding [8, 10-14, 16, 17, 19, 21-24, 26, 28, 30, 31, 38, 39, 43, 48, 50, 55, 58, 61], which resulted in death in one case [58]. Ten patients reportedly had di culty with hemostasis during biopsy or surgery [10,22,26,38,48,52,61,63,66] .Three patients underwent preoperative vascular embolization or ligation, which did not lead to complications during surgery [15,19,26]. Our experience with the present patient also indicated that preoperative vascular embolization is helpful in preventing massive hemorrhage during surgery for pulsatile oral metastasis of RCC.…”
Section: Discussionmentioning
confidence: 99%
“…In Calabar, South-Southern Nigeria it was found to account for 2.27% of adult urological malignancies in a study carried out in 2018 (Isiwele, E. M. et al, 2018). Renal cell carcinoma commonly metastasizes to the lungs, liver, bones and lymph nodes but less commonly to the head and neck region (Kelles, M. et al, 2012;& Altunsoy, E. et al, 2019). It is the third most common infraclavicular neoplasm that metastasizes to the oral cavity, following that of lung and breast carcinoma (Pritchyk, K. M. et al, 2002).…”
Section: Introductionmentioning
confidence: 99%